2015
DOI: 10.1152/ajpregu.00051.2015
|View full text |Cite
|
Sign up to set email alerts
|

Central mechanisms regulating coordinated cardiovascular and respiratory function during stress and arousal

Abstract: Actual or potentially threatening stimuli in the external environment (i.e., psychological stressors) trigger highly coordinated defensive behavioral responses that are accompanied by appropriate autonomic and respiratory changes. As discussed in this review, several brain regions and pathways have major roles in subserving the cardiovascular and respiratory responses to threatening stimuli, which may vary from relatively mild acute arousing stimuli to more prolonged life-threatening stimuli. One key region is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 167 publications
(212 reference statements)
5
117
0
1
Order By: Relevance
“…Moreover, they demonstrated that vmPFC and ACC associations with HR reactivity were mediated (statistically accounted for) by concurrent changes in the PAG and thalamus, thus potentially defining a forebrain-to-subcortical pathway for stressor-evoked cardiovascular (HR) reactivity. These findings agree with neuroanatomical tracing work in primates and other nonhuman animal models demonstrating projections from the medial prefrontal cortex to the PAG and hypothalamus (Bandler et al, 2000; Dampney, 2015), as well as primate anatomical work on the coritical control of the adrenal medulla (Dum et al, 2016). As noted above, this particular line of work was also extended recently to define a multivariate pattern of neural activity encompassing the vmPFC and other networked limbic regions that reliably predicted individual differences in stressor-evoked HR and sympathetic nervous system reactivity (skin conductance) using multivariate methods (Eisenbarth, Chang, & Wager, 2016).…”
Section: Brain-imaging Studies Of Stressor-evoked Cardiovascular Rsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, they demonstrated that vmPFC and ACC associations with HR reactivity were mediated (statistically accounted for) by concurrent changes in the PAG and thalamus, thus potentially defining a forebrain-to-subcortical pathway for stressor-evoked cardiovascular (HR) reactivity. These findings agree with neuroanatomical tracing work in primates and other nonhuman animal models demonstrating projections from the medial prefrontal cortex to the PAG and hypothalamus (Bandler et al, 2000; Dampney, 2015), as well as primate anatomical work on the coritical control of the adrenal medulla (Dum et al, 2016). As noted above, this particular line of work was also extended recently to define a multivariate pattern of neural activity encompassing the vmPFC and other networked limbic regions that reliably predicted individual differences in stressor-evoked HR and sympathetic nervous system reactivity (skin conductance) using multivariate methods (Eisenbarth, Chang, & Wager, 2016).…”
Section: Brain-imaging Studies Of Stressor-evoked Cardiovascular Rsupporting
confidence: 87%
“…The brain has long been implicated in the control of cardiovascular function, particularly in linking stressful experiences to cardiovascular changes associated with clinical events and disease pathophysiology (for reviews see Dampney, 2015; Lane et al., 2009a; 2009b; Palma & Benarroch, 2014; Taggart et al, 2016; Esler, 2017). For example, Cannon originally proposed that intense emotions, such as fright, were generated in the brain and triggered peripheral physiological responses that could end one’s life in “voodoo death” (Cannon, 1928; 1942).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented that the DMH is an important node in sympathoexcitatory responses, in particular following psychological stress (for reviews, see refs. 48,52,53). A key component of this stress-induced descending pathway includes the RVLM (33,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiological interactions between higher cognitive brain structures to the PAG have not been demonstrated. Although, there are no monosynaptic connections between the hippocampus and PAG, forebrain structures have the capacity to engage the brainstem through a variety of relay nuclei (Dampney, 2015). Thus, it was hypothesised that the hippocampus-amygdala axis may be a circuit through which motor and autonomic changes could occur.…”
Section: Significant Findings and Possible Implicationsmentioning
confidence: 99%
“…Based on the ability to modulate cardiorespiratory activities, the amygdala is part of the proposed central autonomic network (Dampney et al, 2002;Dampney, 2015). This argument is supported by projections from the CeA to the dorsomedial hypothalamus (Ono et al, 1985), sympathetic preganglionic neurones in the nucleus ambiguus and rostral ventrolateral medulla (Jongen- Relo and Amaral, 1998;Oka et al, 2008), and parasympathetic neurones in the dorsal motor nucleus of the vagus (Takeuchi et al, 1983).…”
Section: Introductionmentioning
confidence: 98%